What Threat The Campaign Against “Gender Ideology” (Glocalism: Journal of Culture, Politics and Innovation, 2019)
The idea of gender ideology emerged in the 1990s when the Roman Catholic Family Council warned against the idea of “gender” as a threat to the family and to biblical authority. In subsequent years, gender has become an issue in several major elections all over the world. Gender is understood as a single “ideology” that refutes the reality of sexual difference and that seeks to appropriate the divine power of creation for those who wish to create their own genders. Today the defense of the natural and normative character of the heterosexually organized family, linked with the insistence that reproduction requires heterosexuality and the privileged power of the father within the family, becomes an especially intense political issue where state-funded social services to families have been decimated and dependency on Churches has increased for basic services to those abandoned by the state. Significantly, the radical changes in economic life, including the loss of basic structures of social welfare produce a heightened sense of precarity and fear among popu- lations who are then told that it is “gender ideology” that is breaking apart the family, destroying heterosexuality as a natural law, threatening both God’s creative powers and civilization itself. In this paper, I would suggest that we understand the historical formulation of neoliberalism and financialization (the imperative to increase assets at the expense of securing fair wages) not as the cause of the anti-gender ideology movement, but as part of the complex scene of heightened conflict where nationalism, racism, and heightened militarism ally with anti-gender ideology propaganda.
Keywords: gender; ideology; neoliberalism; financialization; social welfare